Effects of iso-butanol additives in ethanol-gasoline blend (E10) on engine performance and exhaust emissions of a multi-cylinder spark-ignition engine / Muhammad Syarifuddin Mohamed Zaharin - Mohamed Zaharin, Muhammad Syarifuddin (2018)
Modern life requirements have been related to the increased of energy consumption, in which major part of the consumption is focusing on the automotive industries. Limited sources of fossil fuel and increasing concerns on environmental issues due to the high emissions of unburned hydrocarbon (HC), carbon monoxide (CO), carbon dioxide (CO2) and nitrogen oxide (NOx) have attracted the attention of researchers and scientists to investigate alternative fuel, especially alcohol. One of the familiar names in the alcohol group is ethanol; a two carbon chains alcohol with a high oxygen content and latent heat of vaporization. Vast research studies in recent years have been triggered to examine the feasibility of ethanol as a blended fuel with pure gasoline at a different blend ratios and varieties of engines' operating conditions to find the optimum results in spark-ignition (SI) engines. It was found from literatures that there is still improvement need to be performed due to the low calorific value of ethanol. Thus, this study aims to examine the properties of iso-butanol additives at three volume percentages; 5%, 10% and 15% in E10 blended fueldenoted as E10B5, E10B10, and El OB 15, respectively. An experimental characterization for the properties of calorific value, kinematic viscosity and density for the fuel samples was carried out according to the specified standard methods of ASTM D240, ASTM D445 and ASTM D4052, respectively. The results of kinematic viscosity and density showed an increasing pattern for the iso-butanol additives in E10 fuel blend compared with those of E10 fuel blend and pure gasoline fuel, while showing a decreasing pattern for the results of heating value. In terms of engine testing operation, the investigation was conducted using a four-cylinder, four-stroke, naturally aspirated, SI engine at half and full open throttle position with a wide range of engine speed from 1000 to 5000 rpm.